Efficacy and safety of fluoxetine monotherapy in bipolar depression: a systematic review. (June 2013) - Martinotti, Giovanni; Sepede, Gianna; Signorelli, Maria; Aguglia, Eugenio; Di Giannantonio, Massimo
<x xml:space="preserve">Abstract</x> Introduction: The treatment of depressive episodes in bipolar disorder (BD) remains a challenge for clinicians and is a hot topic in current psychiatric practice. In the present review, we focused on efficacy and safety of <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=fluoxetine&logicalOpe1=OR&field2=articletitle&text2=fluoxetine&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">fluoxetine monotherapy in order to identify published randomized double-blind trials and open-label trials, written in English, reporting the outcome of fluoxetine treatment in depressed bipolar patients. Areas covered: We searched Pubmed to identify published randomized double-blind trials and open-label trials, written in English, reporting the results of fluoxetine treatment in depressed bipolar patients. The following key words were used: fluoxetine AND bipolar AND depression AND treatment. A total number of seven prospective studies (four randomized clinical trials and three open-label trials) and one two-phase retrospective study were reviewed. Expert opinion: Fluoxetine showed to be efficacious in bipolar depression, confirming its well-known activity in major depressive episodes, with a low percentage of mood switch, despite the general view that antidepressants may increase the rate of manic/hypomanic episodes in BDs. More studies with larger sample sizes, comparing fluoxetine with other antidepressants, mood stabilizers and antipsychotics are needed.